Navigating the Digital Frontier: Organizational Readiness and the Moderating Role of Government Support in Batik SMEs’ Digital Transformation - Wiwiek Rabiatul Adawiyah; Rahab; Leni Susanti (Global Research Collaboration, 2026)
Small and Medium Enterprises (SMEs) represent a cornerstone of economic development, yet they face significant barriers when implementing digital transformation strategies. Contemporary discourse has shifted from debating the necessity of digital transformation to evaluating organizational readiness for technological adoption. This study examines the governmental role in facilitating digital transformation among Batik-producing SMEs through a methodical assessment of readiness dimensions that enhance transformation preparedness. The research employed purposive sampling, collecting 180 responses from Batik sector SMEs through both electronic and traditional survey instruments. Structural equation modeling via SmartPLS 3 was utilized to analyze three hypothesized relationships. Results indicate that technological readiness constitutes the strongest dimension of organizational preparedness, while non-financial governmental support emerged as the most impactful intervention mechanism. Notably, financial support exerted a statistically significant yet negative moderating effect on the relationship between firm readiness and digital transformation outcomes, indicating that it weakens rather than strengthens this relationship. All identified readiness dimensions demonstrated significant direct effects on organizational preparedness for digital initiatives. These findings contribute to the scholarly understanding of digital transformation dynamics in the SME sector and provide evidence-based insights for policymakers seeking to design effective support mechanisms that enhance SMEs’ technological adoption capabilities.